Prevalence of Protozoan and Helminths Parasitic Infection in Palpa, Nepal - Nepali, Pit Bahadur; Shrestha, Santoshi; Rana, Hira Bahadur (Tribhuvan Journal, 2023)
In rural areas of underdeveloped countries, the parasitic infestation is a major public health issue for children and the elderly. The purpose of this study was to determine the prevalence of parasite infestations and risk variables related to Palpa parasitic infestations. The population sample was selected from the Tansen area's usual population, as determined by randomized cluster sampling. A total of 700 samples were collected, with 280 persons from urban regions and 420 from rural areas, for a total of 100 people from various categories in each health center. Data were collected for each person based on their age, gender, and place of residence (urban or rural), as well as through a semi-structured questionnaire and a personal interview. Each health center's laboratory technician team conducted the microscopic investigation of samples (blood, urine, and feces). Five protozoal and six helminth parasites were found among the 11 parasites, with eight kinds of gastrointestinal parasites and three species of blood parasites. The most frequent parasites were discovered to be Entamoeba histolytica, Giardia lamblia, and Ascaris lumbricoides. Females and those who live in rural areas are more likely to be parasite-infested. Prevalence was highest among children under the age of 15 and the elderly. Administrators, health experts, and the community need to approve improvements in the living environment and cleaning practices to break the transmission cycle of parasitic illnesses, health education, and community approval.